ANALYSIS OF THE DESIGN FLOOD DISCHARGE OF THE BRANG BIJI RIVER SUMBAWA REGENCY - Ari Ramadhan Hidayat; Purnama Irwansyah; Muhammad Khalis Ilmi (Fakultas Teknik Sipil dan Perencanaan, 2024)
Sumbawa Regency is one of the districts/cities in West Nusa Tenggara Province that frequently experiences flooding. One of them is the Brang Biji River which is in the Sumbawa River Basin (DAS). Seeing the huge impact of flooding, efforts need to be made to minimize the risks caused by flood disasters. Based on this, this research aims to determine the magnitude of the design flood discharge on the Brang Biji River in Sumbawa district. The magnitude of this design flood discharge can be used to determine plans for future mitigation efforts. The method used in this research is changing daily rainfall data into discharge data. The method used to calculate the design flood discharge is the Nakayasu Synthetic Unit Hydrograph (HSS) method. The research results obtained were flood discharge at return periods of 2, 5, 10, 25, and 50 years using the Nakayasu Synthetic Unit Hydrograph (HSS) method, obtained peak discharge values ​​Q2th = 104,756 m3/second, Q5th = 163,534 m3/second, Q10th = 211,654 m3/second, Q25th = 284,149 m3/second and Q50th = 347,537 m3/second on average occurred in the 4th hour.